Pelatihan Penggunaan Software Accurate sebagai Upaya Knowledge Transfer kepada Karyawan Baru di J&T Cargo Sub 19 - Salsabila Aulia Khinzki, Shiera; Majid, Nurkholish (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This community service activity, involving knowledge transfer, aims to prepare human resources, particularly new employees at J&T Cargo SUB 19, to acquire the technical competency to operate the Accurate Online system. This preparation is crucial for facilitating the independent takeover of the company's administrative and financial tasks. Implementation methods included coordinating initial preparations, implementing shadowing (mentoring and direct observation), field practice simulations, and remote monitoring. This activity focused exclusively on one participant projected to fill this strategic position, with the main content covering invoice creation and payment procedures, inputting daily operational expenses, and recording and reconciling bank transfers. The results of the activity demonstrated a positive impact; through systematic and structured training stages, participants successfully mastered the application's workflow and were able to implement it within the fast-paced daily operational rhythm of a logistics company. Based on descriptive evaluations conducted continuously until the handover deadline, participants demonstrated significant progress, both in terms of data input accuracy and work independence. The success of this training program ensures that the takeover process can proceed smoothly without triggering administrative bottlenecks or disrupting J&T Cargo SUB 19's daily logistics activities.